Imposter Syndrome Among Surgeons Is Associated With Intolerance of Uncertainty and Lower Confidence in Problem Solving. Issue 4 (6th April 2023) - Lin, Eugenia; Crijns, Tom J.; Ring, David; Jayakumar, Prakash; ,
Abstract: Background: Feelings of imposter syndrome (inadequacy or incompetence) are common among physicians and are associated with diminished joy in practice. Identification of modifiable factors associated with feelings of imposter syndrome might inform strategies to ameliorate them. To this point, though, no such factors have been identified. Question/purpose: Are intolerance of uncertainty and confidence in problem-solving skills independently associated with feelings of imposter syndrome after accounting for other factors? Methods: This survey-based experiment measured the relationship between feelings of imposter syndrome, intolerance of uncertainty, and confidence in problem-solving skills among musculoskeletal specialist surgeons. Approximately 200 surgeons who actively participate in the Science of Variation Group, a collaboration of mainly orthopaedic surgeons specializing in upper extremity illnesses primarily across Europe and North America, were invited to this survey-based experiment. One hundred two surgeons completed questionnaires measuring feelings of imposter syndrome (an adaptation of the Clance Imposter Phenomenon Scale), tolerance of uncertainty (the Intolerance of Uncertainty Scale-12), and confidence in problem-solving skills (the Personal Optimism and Self-Efficacy Optimism questionnaire), as well as basic demographics. The participants were characteristic of other Science of Variation Group experiments: the mean age was 52 ± 5 years, with 89% (91 of 102) being men, most self-reported White race (81% [83 of 102]), largely subspecializing in hand and/or wrist surgery (73% [74 of 102]), and with just over half of the group (54% [55 of 102]) having greater than 11 years of experience. We sought to identify factors associated with greater feelings of imposter syndrome in a multivariable statistical model. Results: Accounting for potential confounding factors such as years of experience or supervision of trainees in the multivariable linear regression analysis, greater feelings of imposter syndrome were modestly associated with higher intolerance of uncertainty (regression coefficient [β] 0.34 [95% confidence interval (CI) 0.16 to 0.51]; p < 0.01) and with lower confidence in problem-solving skills (β -0.70 [95% CI -1.0 to -0.35]; p < 0.01). Conclusion: The finding that feelings of imposter syndrome may be modestly to notably associated with modifiable factors, such as difficulty managing uncertainty and lack of confidence in problem-solving, spark coaching opportunities to support and sustain a surgeon's mindset, which may lead to increased comfort and joy at work. Clinical Relevance: Beginning with premedical coursework and throughout medical training and continuing medical education, future studies can address the impact of learning and practicing tactics that increase comfort with uncertainty and greater confidence in problem solving on limiting feelings of imposter syndrome.